English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

solve for x.

27^1-x = (1/9)^2-x



27 has an exponent of 1-x
(1/9) has an exponent of 2-x


I got x = 7/5.

2007-01-11 13:51:02 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

27^(1-x) = (1/9)^(2-x)
because 27 is 3^3 and (1/9) is 3^(-2) so we can use basic number 3 to solve this question
3^3(1-x) = 3^(-2)(2-x)
3^(3-3x) = 3^(-4+4x)

then solve the exponent only
3-3x = -4+4x
3+4 = 2x + 3x
7 = 5x
5x = 7
x = 7/5

2007-01-11 14:00:14 · answer #1 · answered by Rini 1 · 0 0

27^(1-x) = 3^(3-3x)

(1/9)^(2-x) = 3^(-4+2x)

3-3x = -4+2x

5x = 7

x = 7/5

2007-01-11 21:55:31 · answer #2 · answered by bozo 4 · 0 0

fedest.com, questions and answers